1989
DOI: 10.1242/dev.106.4.685
|View full text |Cite
|
Sign up to set email alerts
|

Mouse neural crest cells secrete both urokinase-type and tissue-type plasminogen activators in vitro

Abstract: Neural tubes of E8-5 day mouse embryos were dissected and cultured in serum substitute-supplemented medium to allow the emigration of neural crest cells. After 48 h of culture the neural tubes were removed. The neural crest cells were then cultured for 12 h in serum-free medium, and their culture supernatant was studied by electrophoresis and zymography. The cultured cells were shown to secrete both urokinase-type and tissue-type plasminogen activators. When the truncal neural tube was divided in four equal se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Subsequent studies by other laboratories showed that mouse NC cells secrete urokinase and tissue plasminogen activators (uPA and tPA) into the culture medium ( Menoud et al, 1989 ) and that uPA promotes chick NC migration in vitro via activation of plasmin and TGFβ signaling ( Brauer and Yee, 1993 ; Agrawal and Brauer, 1996 ). Mutations in the lectin complement pathway gene MASP1/3, encoding for Mannose-associated serine protease-1 and -3, cause 3MC (Mingarelli, Malpuech, Michels and Carnevale) syndrome, a rare autosomal recessive disorder that is characterized by a spectrum of developmental features including craniofacial abnormalities ( Rooryck et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies by other laboratories showed that mouse NC cells secrete urokinase and tissue plasminogen activators (uPA and tPA) into the culture medium ( Menoud et al, 1989 ) and that uPA promotes chick NC migration in vitro via activation of plasmin and TGFβ signaling ( Brauer and Yee, 1993 ; Agrawal and Brauer, 1996 ). Mutations in the lectin complement pathway gene MASP1/3, encoding for Mannose-associated serine protease-1 and -3, cause 3MC (Mingarelli, Malpuech, Michels and Carnevale) syndrome, a rare autosomal recessive disorder that is characterized by a spectrum of developmental features including craniofacial abnormalities ( Rooryck et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies by other laboratories showed that mouse NC cells secrete urokinase and tissue plasminogen activators (uPA and tPA) into the culture medium (Menoud et al, 1989) and that uPA promotes chick NC migration in vitro via activation of plasmin and TGFb signaling (Brauer and Yee, 1993;Agrawal and Brauer, 1996). Mutations in the lectin complement pathway gene MASP1/3, encoding for Mannose-associated serine protease-1 and -3, cause 3MC (Mingarelli, Malpuech, Michels and Carnevale) syndrome, a rare autosomal recessive disorder that is characterized by a spectrum of developmental features including craniofacial abnormalities (Rooryck et al, 2011).…”
Section: Extracellular Proteases In Cell Migrationmentioning
confidence: 99%